Authentic assessment setting the stage - Worondo, Ula; Shapiro, Leah; Magna Systems, Inc.; General Learning Communications (Illinois : Magna Systems Inc., 2004)
This module sets the stage for understanding how children are observed within the context of their play as well as their culture, and how these observations are important to understanding their total development. When children are observed in the Social/Emotional, Cognitive, Physical and Language domains of development, teachers are better able to align assessment with curriculum
Title from title screen
Educational consultant, Leah Shapiro ; camera/editor, Nick Kolias
Narrator: Rhoda Olenick
Keywords: Observation (Educational method); Early childhood education; Child development